(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2017)
تبلورت مفاهيم حقوق الإنسان الحديثة في أعقاب الحرب العالمية الثانية (1939 – 1945م). فبعد أن وضعت الحرب أوزارها، كونت الدول المستقلة منظمة الأمم المتحدة. وأصدرت هذه المنظمة ميثاقها الذي أصبح واحداً من أولى وثائق حقوق الإنسان العالمية. وقد نص ميثاق الأمم المتحدة على تعزيز احترام حقوق الإنسان والحريات الأساسية للناس جميعاً دون تمييز بسبب الجنس أو اللغة أو الدين، ولا تفريق بين الرجال والنساء. ولما خلا الميثاق من قائمة تتناول بالتفصيل حقوق الإنسان فقد أصدرت الأمم المتحدة الإعلان العالمي لحقوق الإنسان في 10 ديسمبر 1948م، الذي تضمن المبادئ الرئيسية للحقوق المدنية والسياسية والاقتصادية والاجتماعية والثقافية والحريات الفردية. جاء تعزيز دور الأمم المتحدة في صيانة حقوق الإنسان، من خلال تبنيها عام 1966 م المعاهدة العالمية للحقوق المدنية والسياسية، والمعاهدة العالمية للحقوق الاقتصادية والاجتماعية والثقافية. وقد وفرت هذه المعاهدات الغطاء والحماية القانونية للكثير من الحقوق التي نص عليها الإعلان العالمي لحقوق الإنسان. وتبنت معاهدات أخرى، منذ ذلك الوقت، قضايا مختلفة مثل معاملة السجناء، ووضع اللاجئين، وحقوق المرأة، وحقوق الطفل. إنّ تطبيق قواعد القانون الدولي، يمكن تحديد تطبيقها على المستويين الوطني الداخلي، وعلى المستوى الدولي، وذلك بالعمل والتأثير المتبادلين من قبل الدول، وبمساعدة الإجراءات الوطنية والدولية. من الضرورة أن يكون هذا عبر عملية تحويل هذه القواعد حسب القانون الوطني المعمول فيه في كل بلد. تطبيق القاعدة القانونية في القانون الوطني يلعب الدور الحاسم في تطبيق القاعدة الدولية في مجال حقوق الإنسان من أجل الالتزام بالمقياس العالمي لحقوق الإنسان من الضرورة تصديق الدول العربية على الاتفاقيات الأساسية لحقوق الإنسان، آخذين بعين الاعتبار خصوصية تاريخ تطور كل بلد. وهذه الأهداف يجب أن تساعد في نشاط المنظمات الدولية والاجتماعية لحقوق الإنسان. The modern concepts of human rights crystallized after the world war It (1939 – 1945).After the war put its heavy load, the independent countries established the united Nations organization. This organization issued its charter which became one of the first documents of the international human rights. The charter stated the promotion of respecting human rights and the basic freedoms of all people without any discrimination because of gender, language or religion, and no difference between men and women. And since the charter lacked a list which deals in detail with the human rights, the united Nations issued the international announcement of the human rights on 10th December, 1948, which included the main principles of civilian, political, economic, social and cultural rights as well as individual freedoms. The reinforcement of the role of the united nations in preserving human rights came through the adoption of the international treaty of civil and political rights and the international treaty of economic, social and cultural rights in the year 1966. Those treaties provided the cover and the legal protection for a lot of rights which the international declaration of the human rights stated. Since then, many other treaties adopted different cases such as the treatment of prisoners, the situation of refugees, women rights and children rights. The application of the rules of the international law can be specified on both the internal national level and the international level through the work and the mutual effect from countries and with the help of national and international procedures. It is necessary that this is done through modifying these rules according to the national law that is applied in each country. The application of the legal rule in the national law plays a crucial role in applying the international rule in the field of human rights. In order to comply with the international criterion of human rights, it is necessary for the Arab countries to ratify the basic agreements of human rights, taking into consideration the peculiarity of the history of the development of each country. These purposes should help in the activity of the international and social organizations of human rights.